How Nano‐Ions Act Like Ionic Surfactants. Issue 21 (3rd March 2020) - Hohenschutz, Max; Grillo, Isabelle; Diat, Olivier; Bauduin, Pierre
Abstract: Recently, nanometric ions were shown to adsorb to hydrated neutral surfaces and to bind to the cavities of macrocyclic molecules with an unexpectedly strong affinity arising from a solvent‐mediated effect named superchaotropicity. We show here that nano‐ions at low concentrations (μm range), similarly to anionic surfactants, induce the spontaneous transformation of a swollen lyotropic lamellar phase of non‐ionic surfactant into a vesicle phase. This transition occurs when the neutral lamellae acquire charges, either by adsorption of the nano‐ions onto, or by anchoring of the ionic surfactant into the lamellae. In contrast to ionic surfactants, nano‐ions strongly dehydrate the neutral surfactant assemblies. As a conclusion, these purely inorganic nanometric ions act as alternatives to the widely used organic ionic surfactants. Abstract : Free of charge : Inorganic nano‐ions were found to act like (organic) ionic surfactants when added to dilute solutions of non‐ionic surfactants, inducing spontaneous vesicle formation by adsorption and thus electrically charging the non‐ionic lamellar phase. Although they are fundamentally different, nano‐ions can serve as alternatives to ionic surfactants.